2009
DOI: 10.1152/ajplung.90590.2008
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of reactive oxygen species by Rac1 or catalase prevents asbestos-induced pulmonary fibrosis

Abstract: The release of reactive oxygen species (ROS) and cytokines by alveolar macrophages has been demonstrated in asbestos-induced pulmonary fibrosis, but the mechanism linking alveolar macrophages to the pathogenesis is not known. The GTPase Rac1 is a second messenger that plays an important role in host defense. In this study, we demonstrate that Rac1 null mice are protected from asbestos-induced pulmonary fibrosis, as determined by histological and biochemical analysis. We hypothesized that Rac1 induced pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 47 publications
3
77
0
Order By: Relevance
“…Cell Culture-WT and Rac1 null macrophages were obtained from WT and Rac1 null mice as described previously (23). Cells were maintained in RPMI 1640 medium containing 10% newborn calf serum, 0.5 mM ␤-mercaptoethanol, and penicillin/streptomycin.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cell Culture-WT and Rac1 null macrophages were obtained from WT and Rac1 null mice as described previously (23). Cells were maintained in RPMI 1640 medium containing 10% newborn calf serum, 0.5 mM ␤-mercaptoethanol, and penicillin/streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…We recently demonstrated that Rac1 activity in alveolar macrophages, via H 2 O 2 production, is required for asbestosinduced pulmonary fibrosis (23). We now investigated the mechanisms for Rac1-mediated ROS signaling focusing on the transcriptional regulation of MMP-9.…”
Section: Matrix Metalloproteinases (Mmps)mentioning
confidence: 99%
See 2 more Smart Citations
“…[57][58][59][60] Conversely, catalase or other antioxidants can also be administered therapeutically, in various pre-clincal models, which then prevents the onset of fibrosis. [61][62][63][64][65][66] In this context, it is interesting to note that activated myofibroblasts are known to produce and secrete hydrogen peroxide, which can have deleterious paracrine effects on adjacent normal epithelial cells. 67 Furthermore, breast cancer patients show systemic evidence of increased oxidative stress and a decreased anti-oxidant defense, which increases with aging and tumor progression.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%